Using system dynamics to evaluate renewable electricity development in Malaysia. Issue 1 (2014) - Salman Ahmad; Razman bin Mat Tahar
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to provide an assessment of Malaysia's renewable capacity target. Malaysia relies heavily on fossil fuels for electricity generation. To diversify the fuel‐mix, a technology‐specific target has been set by the government in 2010. Considering the complexity in generation expansion, there is a dire need for an assessment model that can evaluate policy in a feedback fashion. The study also aims to expand policy evaluation literature in electricity domain by taking a dynamic systems approach. Design/methodology/approach – System dynamics modelling and simulation approach is used in this study. The model variables, selected from literature, are constituted into casual loop diagram. Later, a stock and flow diagram is developed by integrating planning, construction, operation, and decision making sub‐models. The dynamic interactions between the sub‐sectors are analysed based on the short‐, medium‐ and long‐term policy targets. Findings – Annual capacity constructions fail to achieve short‐, medium‐ and long‐term targets. However, the difference in operational capacity and medium‐ and long‐term target are small. In terms of technology, solar photovoltaic (PV) attains the highest level of capacity followed by biomass. Research limitations/implications – While financial calculations are crucial for capacity expansion decisions, currently they are not being modelled; this study primarily focuses on system delays and exogenous components only. Practical implications – A useful model that offers regulators and investors insights on system characteristics and policy targets simultaneously. Originality/value – This paper provides a model for evaluating policy for renewable capacity expansion development in a dynamic context, for Malaysia. <ack> <x xml:space="preserve"> Acknowledgements </x> The authors would like to acknowledge and thank Universiti Malaysia Pahang for the financial support (GRS 110328) to complete this work. The authors would also like to thank two anonymous reviewers whose suggestions helped to improve this work. </ack>